Early pregnancy angiogenic proteins levels and pregnancy related hypertensive disorders. (4th March 2017) - Jakovljevic, Ana; Bogavac, Mirjana; Lozanov-Crvenkovic, Zagorka; Milosević-Tosic, Mirjana; Nikolic, Aleksandra; Mitic, Gorana
Abstract: Introduction : Normal placental vascular development depends on multiple interactions of many regulatory molecules including pro and antiangiogenic proteins. It is considered that these vascular modulators might be one of the factors responsible for development hypertensive disorders in pregnancy. Objective : To evaluate and compare the early pregnancy (11–14 week of gestation) serum level of angiogenic proteins sFlt1, VEGF i PIGF between different types of pregnancy related hypertensive disorders. Materials and methods : The study included 177 pregnant women between 11 and 14 weeks of gestation, divided into four study subgroups (preeclampsia group-41, gestational hypertension group-31, chronic hypertension group-32 and miscarriage group-19) and control group-54. Blood samples (serum) were taken for measuring sFlt1, VEGF i PIGF by a quantitative ELISA technique and measuring other biochemical and hematological parameters. Results : Significantly higher levels of sFlt1 were in the subgroups with preeclampsia and miscarriages, significantly lower level of VEGF in the all study subgroups and lover level of PIGF were in miscarriage group. In the groups with chronic and gestational hypertension there were higher level of sFlt1 and lover level of VEGF than in the control group, but the differences did not reach statistical significance. Conclusion : Early pregnancy imbalance between antiangiogenic protein sFlt1 and proangiogenic molecules VEGF and PIGF could have impact on pathophysiology of placental disorders which leads to development of pregnancy related hypertensive disorders.